Elucidating the metabolic mechanisms and active constituents of ZuoGui Wan in combatting postmenopausal osteoporosis: A metabolomics and network pharmacology approach - Yanchen Feng; KaiKai Shi; Dingming Li; Shunzhi Yang; Xue Dang; Jinyao Li; Yan Chen; Jianping Yao; Yunke Zhang; Lu Sun; Feixiang Liu (Phytomedicine Plus)
Background: Postmenopausal osteoporosis (PMOP) is a systemic metabolic disease with an imbalance of bone resorption and bone formation coupling as the basic pathogenesis. ZuoGui Wan (ZGW) can effectively ameliorate bone loss associated with decreased estrogen levels, the metabolic mechanisms and active ingredients involved remain unclear. Method: We evaluated the efficacy of ZGW on bone loss in ovariectomized (OVX) rats. The blood-entry components of ZGW were identified using ultra-high performance liquid chromatography-high resolution mass spectrometry. The metabolic mechanisms of ZGW against PMOP were elucidated through metabolomics. Components highly correlated with differential metabolites were identified via correlation analysis. The metabolic mechanism of ZGW against PMOP was further confirmed by combining network pharmacology and metabolomics results and constructing an in vitro cell model for validation. Result: ZGW reversed OVX-induced bone loss by enhancing bone density and improving bone microstructural integrity. Initially, 14 prototype components were identified in the serum of OVX rats following ZGW intervention. Metabolomics analysis revealed 33 differential metabolites involved in pathways such as arginine biosynthesis, and the metabolism of arginine, proline, histidine, aspartate, and glutamate. Additionally, network pharmacology and molecular docking analyses further dissected the active ingredients of ZGW, constructing a ''Compound-Targets-Metabolic pathway-Metabolites'' network against PMOP. Conclusion: this study comprehensively revealed the metabolic mechanism and active ingredients of ZGW against PMOP for the first time, providing a new perspective on the study of the mechanism of ZGW against PMOP.